Market Access and Quality Upgrading: Evidence from Four Field Experiments - Bold, Tessa; Ghisolfi, Selene; Nsonzi, Frances; Svensson, Jakob (American Economic Review, 2022)
Smallholder farming in many developing countries is characterized by low productivity and low-quality output. Low quality limits the price farmers can command and their potential income. We conduct a series of experiments among maize farmers in Uganda to shed light on the barriers to quality upgrading and to study its potential. We find that the causal return to quality is zero. Providing access to a market where quality is paid a market premium led to an increase in farm productivity and income from farming. Our findings reveal the importance of demand-side constraints in limiting rural income and productivity growth. (JEL C93, L14, L15, L22, O13, Q12, Q13)